FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA KARYAWAN OPERATOR PADA PT IKP BOGOR - Sandi Noorzaman Gandrung; Putri Pertiwi (Universitas Pakuan, 2020)
This research aims to determine and analyze the influence of motivation, incentives and organizational culture on employee performance at PT IKP-Bogor. Type of this research uses associative quantitative research, the research analysis is multiple linear regression analysis. The results showed simultaneously that the variables of motivation, incentives and organizational culture had a significant effect on employee performance, while partially the variables that had an effect on employee performance were motivation and organizational culture. The results of the coefficient of determination show the variables of motivation, incentives and organizational culture can explain the employee performance variable by 67%, while the remaining 33% is explained by other variables outside of this research. The implication of this research is that the company is expected to motivate and create an employee-oriented organizational culture.